Perbedaan Kadar Methylglyoxal (MG) Ovarium Tikus Putih (Rattus Norvegicus) Terpajan Kadmium dan Tidak Terpajan Kadmium - Annisa Halida Husna; Eko Suhartono; Meitria Syahadatina Noor (Berkala Kedokteran, 2014)
ABSTRACT: Cadmium (Cd) is a heavy metal nonessensial that can pollute the environment and if it is included into the food chain and fish or plant indirectly also tainted Cd. If fish or plant that is contaminated with Cd consumed persistently by human beings in a long time will accumulate in the body and be chronic toxic by changing structural also functional an organ of the ovary. Determine the level Cd toxic in the ovary with measures level of methylglyoxal (MG). This research using the ovaries of white rats age of 2-3 months. This research to know the difference in the levels of MG of rat ovaries exposed and unexposed Cd. This study is experimental laboratory on the two groups, the control group P(0) that are aquadest as much as 2 ml per day for 4 weeks an exposure group P(1) who is given a Cd with a concentration of 6 mg/L are given as much as 2 ml for 4 weeks. The research results obtained average in the control group P(0) of 0,005 and treatment group P(1) by 0,016. Then to test normality Shapiro-wilk, after a normal, then do a non parametric tests Mann-whitney and meaningful differences between the results obtained by the control group p<0,005. There is a meaningful difference between the control group MG level of P(0) with the treatment group P(1) where the presence of increased levels of MG on Cd exposure groups.